Objective-C for Absolute Beginners iPhone, iPad and Mac Programming Made Easy - Kaczmarek, Stefan (Apress, 2018)
Learn Objective-C and its latest release, and learn how to mix Swift with it. You have a great idea for an app, but how do you bring it to fruition? With Objective-C, the universal language of iPhone, iPad, and Mac apps. Using a hands-on approach, you'll learn how to think in programming terms, how to use Objective-C to construct program logic, and how to synthesize it all into working apps. Gary Bennett, an experienced app developer and trainer, will guide you on your journey to becoming a successful app developer. Along the way you'll discover the flexibility of Apple's developer tools If you're looking to take the first step towards App Store success, Objective-C for Absolute Beginners, Fourth Edition is the place to start.